Positive electrode active material and lithium secondary battery containing the same

By controlling the concentration gradient slope of cobalt in the positive electrode active substance of lithium secondary battery and adopting a core-shell particle structure, the stress accumulation problem caused by volume changes in the positive electrode active substance of lithium secondary battery during charging and discharging is solved, and particle stability and electrochemical characteristics are improved.

CN116031398BActive Publication Date: 2025-03-07ECOPRO BM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211301211.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-26
Filing Date
2022-10-24
Publication Date
2025-03-07
Estimated Expiration
2042-10-24

AI Technical Summary

Technical Problem

The volume change of the positive electrode active substance of the existing lithium secondary battery during charging and discharging leads to stress accumulation, resulting in particle damage and reduced stability, and the uneven coating problem of bimodal positive electrode active substances affects electrochemical characteristics and stability.

Method used

By controlling the gradient slope of cobalt concentration in small and large particles, particle stability is uniformly improved, and core-shell particle structure and specific coating materials are used to alleviate volume changes and stress accumulation.

Benefits of technology

The particle stability and electrochemical characteristics of the positive electrode active substance of lithium secondary battery are improved, and the battery life and charge and discharge efficiency are extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003904199360000251
    Figure BDA0003904199360000251
  • Figure BDA0003904199360000261
    Figure BDA0003904199360000261
  • Figure BDA0003904199360000262
    Figure BDA0003904199360000262
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material and a lithium secondary battery containing the same, and more specifically, to a positive electrode active material, a positive electrode containing the above-mentioned positive electrode active material, and a lithium secondary battery using the above-mentioned positive electrode, wherein the above-mentioned positive electrode active material is a bimodal positive electrode active material comprising a first lithium composite oxide as small particles and a second lithium composite oxide as large particles, wherein the slope of the concentration gradient of cobalt in the above-mentioned small particles and the above-mentioned large particles decreasing from the surface portion to the center portion is controlled, thereby uniformly improving the particle stability of the above-mentioned small particles and the above-mentioned large particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material and a lithium secondary battery containing the same, and more specifically, to a positive electrode active material, a positive electrode containing the above-mentioned positive electrode active material, and a lithium secondary battery using the above-mentioned positive electrode, wherein the above-mentioned positive electrode active material is a bimodal positive electrode active material comprising a first lithium composite oxide as small particles and a second lithium composite oxide as large particles, wherein the slope of the concentration gradient of cobalt in the above-mentioned small particles and the above-mentioned large particles decreasing from the surface portion to the center portion is controlled, thereby uniformly improving the particle stability of the above-mentioned small particles and the above-mentioned large particles. Background Art

[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the difference in chemical potential when lithium ions are inserted / released between the positive and negative electrodes.

[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Lithium composite oxides are used as positive electrode active materials for lithium secondary batteries, and as examples thereof, composite oxides such as LiCoO2, LiMn2O4, LiNiO2, and LiMnO2 are being studied.

[0005] Among the above-mentioned positive electrode active materials, LiCoO2 is widely used due to its excellent life characteristics and charge and discharge efficiency. However, cobalt used as a raw material has limited resources and is expensive, so it has a disadvantage of limited price competitiveness.

[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of excellent thermal stability and low price, but have the problems of small capacity and poor high temperature characteristics. In addition, LiNiO2 positive electrode active material shows battery characteristics of high discharge capacity, but due to the cation mixing problem between Li and transition metals, it is difficult to synthesize, thus having a big problem in rate characteristics.

[0007] In addition, when charging and discharging, the lithium composite oxide contained in the positive electrode active material changes in volume according to the insertion / extraction of lithium ions in the lithium composite oxide. Generally, the lithium composite oxide is in the form of secondary particles formed by the aggregation of multiple primary particles. When charging and discharging, when a rapid volume change of multiple primary particles occurs or stress is accumulated due to repeated charging and discharging, there is a problem of cracks in the secondary particles or collapse or change (phase change) of the crystal structure.

[0008] Such a problem eventually causes a decrease in the stability and reliability of the positive electrode active material, and therefore various studies are being conducted to alleviate the volume change of the lithium composite oxide during charge and discharge or to minimize the stress caused by the volume change to prevent particle damage.

[0009] Moreover, in recent years, in order to increase the capacity of lithium secondary batteries, bimodal positive electrode active materials that mix small particles and large particles with different average particle sizes are often used. In the case of mixing small particles and large particles, small particles with relatively small average particle sizes can fill the pores between large particles, thereby increasing the integrated density of lithium composite oxides per unit volume, thereby increasing the energy density per unit volume. Summary of the invention

[0010] Technical issues

[0011] In the past, in order to prevent particle damage by relieving the volume change of lithium composite oxides or minimizing the stress caused by the volume change during charge and discharge, the aggregation of primary particles was intentionally reduced to allow a predetermined gap between the primary particles, thereby dispersing the stress caused by the volume change of the primary particles. However, such lithium composite oxides have a limitation of reduced energy density per unit volume.

[0012] In the case of a bimodal positive electrode active material, in order to relieve stress applied to small particles and large particles due to repeated charge and discharge, small particles and large particles coated with a predetermined substance may be used.

[0013] At this time, when the mixture of small particles and large particles is mixed with the coating raw material and then heat-treated at the same time, as the coating raw material is biased towards small particles with a relatively large specific surface area, an unbalanced coating problem between small particles and large particles may occur. This leads to an imbalance in particle stability between small particles and large particles in the bimodal positive active material, which may serve as a cause for reducing the electrochemical characteristics and stability of the positive active material.

[0014] In order to reduce the above-mentioned coating heaviness phenomenon, it is possible to consider mixing small particles and large particles with the coating raw material material separately, heat-treating them, and then mixing the coated small particles and large particles. However, in this case, it is difficult to effectively fill the small particles in the large particles, thereby causing a new problem that the integration density of the composite oxide per unit volume and the energy density per unit volume cannot be fully improved.

[0015] Under such circumstances, the present inventors have found that the particle stability of the small particles and the large particles can be uniformly improved by controlling the slope of the concentration gradient of cobalt decreasing from the surface to the center in the small particles and the large particles respectively.

[0016] Therefore, the object of the present invention is to provide a positive electrode active material, which is a bimodal positive electrode active material comprising a first lithium composite oxide as small particles and a second lithium composite oxide as large particles, wherein the first lithium composite oxide and the second lithium composite oxide contain at least nickel and cobalt, and as the cobalt in the first lithium composite oxide and the second lithium composite oxide has a concentration gradient decreasing from the surface portion to the center portion, cracks, collapse of the crystal structure and / or changes in the crystal structure (phase transition) in the surface portion and the center portion of the first lithium composite oxide and the second lithium composite oxide are alleviated or prevented, thereby improving the stability of the particles.

[0017] Furthermore, the object of the present invention is to provide a positive electrode active material, which is a bimodal positive electrode active material comprising a first lithium composite oxide as small particles and a second lithium composite oxide as large particles, wherein the first lithium composite oxide and the second lithium composite oxide contain at least nickel and cobalt, and as the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the first lithium composite oxide is different from the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the second lithium composite oxide, the particle stability of the small particles and the large particles can be uniformly improved.

[0018] Furthermore, another object of the present invention is to provide a positive electrode comprising the positive electrode active material defined in the present application.

[0019] Meanwhile, another object of the present invention is to provide a lithium secondary battery using the positive electrode defined in the present application.

[0020] Solutions to the problem

[0021] According to one aspect of the present invention, there is provided a bimodal positive electrode active material including a first lithium composite oxide as small particles and a second lithium composite oxide as large particles.

[0022] The first lithium composite oxide and the second lithium composite oxide include at least nickel and cobalt, and the cobalt in the first lithium composite oxide and the second lithium composite oxide may have a concentration gradient decreasing from a surface portion toward a center portion.

[0023] At this time, when the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the first lithium composite oxide is set to s1 and the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the second lithium composite oxide is set to s2, the above s1 and the above s2 can satisfy the following formula 1.

[0024] Formula 1: s1<s2

[0025] The first lithium composite oxide and the second lithium composite oxide are composite particles including at least one primary particle. The primary particle may be represented by the following Chemical Formula 1.

[0026] Chemical formula 1: Li w Ni 1-(x+y+z) Co x M1 y M2 z O2

[0027] (Wherein, M1 is at least one selected from Mn and Al, M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W and Cu, M1 and M2 are different from each other, 0.5≤w≤1.5, 0≤x≤0.50, 0≤y≤0.20, 0≤z≤0.20.)

[0028] Furthermore, at least one of the first lithium composite oxide and the second lithium composite oxide is a core-shell particle including a coating layer covering at least a portion of the surface of the primary particle and the composite particle, and the coating layer may include a metal oxide represented by the following Chemical Formula 2.

[0029] Chemical formula 2: Li a M3 b O c

[0030] (Wherein, M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd and Nd, 0≤a≤10, 0≤b≤8, 2≤c≤13, but the case where a and b are both 0 is excluded.)

[0031] Furthermore, according to still another aspect of the present invention, a positive electrode comprising the positive electrode active material defined in the present application is provided.

[0032] Meanwhile, according to another aspect of the present invention, a lithium secondary battery using the positive electrode defined in the present application is provided.

[0033] Effects of the Invention

[0034] The positive electrode active material of various embodiments of the present invention is a bimodal positive electrode active material comprising a first lithium composite oxide as small particles and a second lithium composite oxide as large particles with different average particle sizes. The small particles with relatively small average particle size can fill the pores between the large particles, thereby increasing the integration density of the lithium composite oxide in unit volume, thereby increasing the energy density per unit volume.

[0035] Furthermore, according to the present invention, the slope of the concentration gradient of cobalt in the small particles and the large particles decreasing from the surface toward the center is controlled, thereby uniformly improving the particle stability of the small particles and the large particles. DETAILED DESCRIPTION

[0036] Hereinafter, the positive electrode active material of the present invention and the lithium secondary battery including the positive electrode active material will be described in more detail.

[0037] Positive active material

[0038] According to one aspect of the present invention, there is provided a bimodal positive electrode active material including a first lithium composite oxide as small particles and a second lithium composite oxide as large particles.

[0039] In the present application, the range of the average particle size (D50) of small particles and large particles is not particularly limited, but in order to distinguish whether any lithium composite oxide is a small particle or a large particle, the following standard range of the average particle size (D50) of small particles and large particles can be determined.

[0040] Small particles refer to lithium composite oxides having an average particle size (D50) of 7 μm or less, and large particles refer to lithium composite oxides having an average particle size (D50) of greater than 7 μm. There is no upper limit to the average particle size (D50) of the large particles, but for example, the large particles may have an average particle size greater than 7 μm and less than 30.0 μm.

[0041] The bimodal positive active material of various embodiments of the present invention may be present in a state where the first lithium composite oxide having the average particle size (D50) defined above and the second lithium composite oxide are mixed at a weight ratio of 5:95 to 50:50.

[0042] At this time, the first lithium composite oxide may exist in the form of filling the pores between the second lithium composite oxides, or may also exist in the form of being attached to the surface of the second lithium composite oxide or being aggregated by the first lithium composite oxides. However, it is preferred that at least the pores formed by the plurality of second lithium composite oxides are fully filled by the first lithium composite oxide having a relatively small average particle size.

[0043] When the ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is too small, the pores formed by the second lithium composite oxide are difficult to be fully filled with the first lithium composite oxide. On the contrary, when the ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is too large, as the ratio of the first lithium composite oxide in the positive electrode active material to aggregate increases, there is a concern that the stability of the positive electrode active material may be reduced, such as a reduction in the compression density of the positive electrode active material.

[0044] The first lithium composite oxide and the second lithium composite oxide include at least nickel and cobalt, and the cobalt in the first lithium composite oxide and the second lithium composite oxide may have a concentration gradient decreasing from a surface portion toward a center portion.

[0045] The first lithium composite oxide and the second lithium composite oxide are composite particles including at least one primary particle. The primary particle may be represented by the following Chemical Formula 1.

[0046] Chemical formula 1: Li w Ni 1-(x+y+z) Co x M1 y M2 z O2

[0047] (Wherein, M1 is at least one selected from Mn and Al, M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W and Cu, M1 and M2 are different from each other, 0.5≤w≤1.5, 0≤x≤0.50, 0≤y≤0.20, 0≤z≤0.20.)

[0048] Furthermore, the first lithium composite oxide and / or the second lithium composite oxide may be a high-Ni type lithium composite oxide including primary particles whose concentrations (molar percentage) of Ni, Co, M1 and M2 in Chemical Formula 1 satisfy the following Relationship 1.

[0049] Relationship 1: Ni / (Ni+Co+M1+M2)≥80.0

[0050] Furthermore, the above-mentioned first lithium composite oxide and / or the above-mentioned second lithium composite oxide can be a high-Ni / low-Co (low-Co) type lithium composite oxide comprising the following initial particles: in the above-mentioned chemical formula 1, the concentrations (molar percentages) of Ni, Co, M1 and M2 satisfy the above-mentioned relationship 1, and at the same time, the Co content is less than 10 molar percentages, preferably less than 5 molar percentages.

[0051] Generally, it is known that in a lithium composite oxide containing at least nickel and cobalt, as the content of Ni increases, structural instability of the lithium composite oxide caused by Li / Ni cation mixing may occur. In addition, it is reported that in a lithium composite oxide containing at least Ni and Co, as the content of Co decreases, the initial overvoltage (resistance) increases, thereby inevitably reducing efficiency characteristics.

[0052] However, as the lithium composite oxide contained in the positive electrode active material of one embodiment of the present invention has a concentration gradient in which the concentration of cobalt decreases from the surface portion toward the center portion of the above-mentioned lithium composite oxide, the structural instability and reduction in efficiency characteristics of the high-Ni or high-Ni / low-Co type lithium composite oxide can be alleviated and / or prevented.

[0053] In addition, the lithium composite oxide contained in the positive electrode active material defined in the present application may be a secondary particle including at least one type of primary particle.

[0054] Here, "secondary particles comprising at least one type of primary particles" should be interpreted as including both "particles formed by the aggregation of multiple primary particles" and "particles comprising a single primary particle in a non-aggregated form".

[0055] The primary particles and the secondary particles may each independently have a rod-like, elliptical and / or irregular shape.

[0056] When the average major axis length is used as an index showing the size of the primary particles and the secondary particles, the average major axis length of the primary particles constituting the lithium composite oxide may be 0.1 μm to 5 μm, and the average major axis length of the secondary particles may be 1 μm to 30 μm. The average major axis length of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles, and the positive electrode active material may include particles having various average major axis lengths.

[0057] In the case where the above-mentioned lithium composite oxide is "particles in a non-aggregated form containing a single primary particle" or "particles formed by aggregation of a smaller number of primary particles", the size (average particle size) of the primary particles contained in the "particles in a non-aggregated form containing a single primary particle" or "particles formed by aggregation of a smaller number of primary particles" may be larger than the size (average particle size) of the primary particles contained in the "secondary particles formed by aggregation of tens to hundreds or more primary particles".

[0058] As described above, compared to the usual preparation of "secondary particles formed by the aggregation of tens to hundreds or more primary particles", lithium composite oxides that are "particles in a non-aggregated form containing a single primary particle" or "particles formed by the aggregation of a smaller number of primary particles" require strong heat treatment conditions (high heat treatment temperature / long heat treatment time).

[0059] It is known that when heat treatment is performed for a long time at a relatively high temperature (for example, 800° C. or higher), particle growth (crystal growth) is promoted, thereby increasing the size of single particles and obtaining a positive electrode active material with reduced particle aggregation.

[0060] For example, when the lithium composite oxide is a "non-aggregated particle including a single primary particle" or a "particle formed by a small number of primary particles", the average major axis length of the primary particles may be in the range of 0.5 μm to 20 μm. On the contrary, when the lithium composite oxide is a "particle formed by a plurality of (tens to hundreds or more) primary particles", the average major axis length of the primary particles may be in the range of 0.1 μm to 5 μm.

[0061] Furthermore, the primary particles may include at least one type of crystallite. That is, the primary particles may be composed of a single crystallite or may exist as particles including a plurality of crystallites.

[0062] In one embodiment, at least one of the first lithium composite oxide and the second lithium composite oxide is a core-shell particle including a coating covering at least a portion of the surface of the primary particle and the composite particle, and the coating may include a metal oxide represented by the following Chemical Formula 2.

[0063] Chemical formula 2: Li a M3 b O c

[0064] (Wherein, M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd and Nd, 0≤a≤10, 0≤b≤8, 2≤c≤13, but the case where a and b are both 0 is excluded.)

[0065] The coating layer may be in a form where different metal oxides exist simultaneously in one layer or different metal oxides represented by the chemical formula 2 exist in separate layers. Also, the coating layer may include a metal oxide containing at least Co.

[0066] The metal oxide represented by the chemical formula 2 may be physically and / or chemically combined with the primary particles and / or the secondary particles. Furthermore, the metal oxide may exist in a state of forming a solid solution with the primary particles and / or the secondary particles.

[0067] The metal oxide is an oxide formed by a complex of lithium and an element represented by M3 or an M3 oxide. The metal oxide may be, for example, Li a W b O c , Li a Zr b O c , Li a Ti b O c , Li a Ni b O c , Li a B b O c , Li a Co b O c , Li a Al b O c 、Co b O c 、Al b O c , W b O c 、Zr b O c 、Ti b O c or B b O c The above examples are merely provided for ease of understanding, and the metal oxides defined in the present application are not limited to the above examples.

[0068] Furthermore, the metal oxide is an oxide formed by a complexation of lithium and at least two elements represented by M3, or may further include a metal oxide formed by a complexation of lithium and at least two elements represented by M3. The metal oxide formed by a complexation of lithium and at least two elements represented by M3 may be, for example, Li a (W / Ti) b O c , Li a (W / Zr) b O c , Li a (W / Ti / Zr) b O c , Li a (W / Ti / B) b O c etc., but not limited to these.

[0069] The concentration gradient pattern shown by the cobalt in the first lithium composite oxide and the second lithium composite oxide contained in the positive electrode active material of the present application can be formed by the coating. That is, the concentration gradient shown by the cobalt in the first lithium composite oxide and the second lithium composite oxide can be achieved by the concentration of cobalt present in the primary particles and / or secondary particles and the concentration of cobalt present in the metal oxide, and the metal oxide is present on the surface of the primary particles and / or secondary particles.

[0070] The concentration of the transition metal in the first lithium composite oxide and the second lithium composite oxide can be measured by various known methods. For example, after the first lithium composite oxide and the second lithium composite oxide are subjected to cross-sectional processing, the concentration of the target transition metal is analyzed by EDS mapping and line scanning. In this case, the concentration change of the target transition metal can be confirmed from the surface of the first lithium composite oxide and the second lithium composite oxide toward the center.

[0071] The method comprises the following energy analysis-energy dispersive X-ray spectroscopy method: by changing the acceleration voltage (V acc ), and measuring the concentration of the target transition metal accumulated from the surface of the above-mentioned lithium composite oxide to a specific depth penetrated by the electron beam at each accelerating voltage.

[0072] In the present application, the concentration of transition metals is analyzed by the aforementioned energy analysis-energy dispersive X-ray spectroscopy method. Specifically, after the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) contained in the positive electrode active material of the present application are screened respectively, the acceleration voltage of the electron beam irradiated to the surface of the screened first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) is changed from 1kV to 30kV (1kV, 3kV, 5kV, 7.5kV, 10kV, 12.5kV, 15kV, 20kV, 30kV), and the cumulative concentration (at%) of the transition metal from the surface of the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) to the specific depth penetrated by the electron beam of each acceleration voltage can be analyzed.

[0073] For example, when the electron beam can penetrate from the surface of the first lithium composite oxide and the second lithium composite oxide to a depth of about 300 nm by irradiating the surface of the first lithium composite oxide and the second lithium composite oxide with an electron beam having an accelerating voltage of 10 kV, the concentration of the target transition metal present in the region from the surface of the first lithium composite oxide and the second lithium composite oxide to a depth of 300 nm can be measured by the energy analysis-energy dispersive X-ray spectrometry. Furthermore, when the electron beam can penetrate from the surface of the first lithium composite oxide and the second lithium composite oxide to a depth of about 800 nm by irradiating the surface of the first lithium composite oxide and the second lithium composite oxide with an electron beam having an accelerating voltage of 20 kV, the concentration of the target transition metal present in the region from the surface of the first lithium composite oxide and the second lithium composite oxide to a depth of 800 nm can be measured by the energy analysis-energy dispersive X-ray spectrometry.

[0074] That is, it can be interpreted that when the measured cumulative concentration of the target transition metal decreases with the increase of the acceleration voltage of the electron beam irradiating the surface of the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide, the concentration of the target transition metal has a gradient decreasing from the surface portion toward the center portion of the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide.

[0075] When energy analysis-energy dispersive X-ray spectroscopy analysis is performed, the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide can both show a concentration gradient in which the concentration of cobalt decreases from the surface to the center. In the energy analysis-energy dispersive X-ray spectroscopy, for the surfaces of the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) contained in the positive electrode active material of the present application, the cumulative concentration of cobalt from the surface of the above-mentioned secondary particles to the depth penetrated by the above-mentioned electron beam is measured using an electron beam irradiated with an accelerating voltage increased from 1 kV to 30 kV.

[0076] The concentration gradient in which the concentration of cobalt in the first lithium composite oxide and the second lithium composite oxide decreases from the surface portion toward the center portion also exists when the first lithium composite oxide and the second lithium composite oxide are core-shell particles. In this case, there may be a concentration gradient in which the concentration of cobalt decreases from the shell toward the cobalt.

[0077] At this time, the concentration gradient of the cobalt may be a concentration gradient in which the concentration of the cobalt decreases continuously or discontinuously from the surface portion toward the center portion of the particle. That is, when the concentration of the cobalt decreases from the starting point to the end point in any interval in which the concentration of the cobalt is measured, the cobalt may have a concentration gradient that decreases from the starting point to the end point in the above-mentioned arbitrary interval.

[0078] However, in this case, the slopes of the cobalt concentration gradients shown by the first lithium composite oxide and the second lithium composite oxide may be different from each other.

[0079] At this time, preferably, when the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the first lithium composite oxide is set to s1 and the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the second lithium composite oxide is set to s2, the above s1 and the above s2 satisfy the following formula 1.

[0080] Formula 1: s1<s2

[0081] Furthermore, the slopes of the cobalt concentration gradients shown in the first lithium composite oxide and the second lithium composite oxide are independent of each other or have the same sign, and thus the directions of the cobalt concentration gradients are the same.

[0082] The above formula 1 means that the slope of the concentration gradient of cobalt in the second lithium composite oxide as large particles is greater than the slope of the concentration gradient of cobalt in the first lithium composite oxide as small particles.

[0083] The large slope of the concentration gradient means that the final cobalt concentration decreases greatly from the surface portion to the center portion of the particle. Under the premise that the cobalt content in the first lithium composite oxide and the second lithium composite oxide is the same, when the slope of the concentration gradient of the cobalt concentration decrease in the second lithium composite oxide is large, it can be predicted that the cobalt in the second lithium composite oxide is relatively concentrated in the surface portion compared to the cobalt in the first lithium composite oxide.

[0084] However, in the case where the cobalt content in the second lithium composite oxide is greater than the cobalt content in the first lithium composite oxide, even if the slope of the concentration gradient in which the cobalt concentration in the second lithium composite oxide decreases is large, the cobalt content in the central portion of the second lithium composite oxide may be greater than or similar to the cobalt content in the central portion of the first lithium composite oxide.

[0085] For example, in order to form core-shell particles, instead of coating the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide separately, when the above-mentioned first lithium composite oxide (or its precursor) and the above-mentioned second lithium composite oxide (or its precursor) are mixed with the raw material of the metal oxide represented by the above-mentioned Chemical Formula 2 and then heat-treated, the coated raw material can be biased towards the above-mentioned first lithium composite oxide which is small particles with a relatively large specific surface area and a small grain boundary density.

[0086] For the coating formed on the surface of the aforementioned lithium composite oxide, when charging and discharging, the volume change of the lithium composite oxide is alleviated, or the stress generated according to the volume change is minimized, thereby playing a role in preventing damage to the particles. However, in the case where the coating raw material is biased towards the above-mentioned first lithium composite oxide, the deviation in particle stability between the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide is greater.

[0087] Furthermore, in the case of the first lithium composite oxide having a relatively small particle size and a small grain boundary density, it is easier to form a coating on the interior of the secondary particles, that is, on the surface of the primary particles, than on the second lithium composite oxide. Therefore, when the coating raw material is biased towards the first lithium composite oxide, a deviation in the stability of the primary particles in the surface and center of the second lithium composite oxide may occur.

[0088] Therefore, in the surface and center portions of the first lithium composite oxide and the second lithium composite oxide, in order to uniformly improve the stability of the particles by alleviating or preventing the generation of cracks, the collapse of the crystal structure and / or the change of the crystal structure (phase change), preferably, the absolute value s1 of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the first lithium composite oxide and the absolute value s2 of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the second lithium composite oxide should satisfy a prescribed relationship.

[0089] More specifically, the above-mentioned s1 can be the absolute value of the slope of the cobalt concentration gradient measured in the region where the acceleration voltage of the electron beam irradiated to the surface of the above-mentioned first lithium composite oxide is from 1 kV to 30 kV, and the above-mentioned s2 can be the absolute value of the slope of the cobalt concentration gradient measured in the region where the acceleration voltage of the electron beam irradiated to the surface of the above-mentioned second lithium composite oxide is from 1 kV to 30 kV, but it is not limited to this. The slope of the cobalt concentration gradient in the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide can be an absolute value measured in a specified area along the direction from the surface portion (shell) of the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide toward the center portion (core).

[0090] In one embodiment, s1, which is an absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the first lithium composite oxide, may satisfy the following formula 2.

[0091] Formula 2: 0.5<s1<2.0

[0092] The fact that s1, which is the absolute value of the slope of the concentration gradient of cobalt in the first lithium composite oxide, is 0.5 or less means that there is almost no concentration deviation of cobalt from the surface portion toward the center portion of the first lithium composite oxide. In other words, it means that the amount of cobalt in the first lithium composite oxide is insufficient. In this case, the effect of improving the stability of the initial particles existing in the surface portion of the first lithium composite oxide and the region relatively close to the center portion of the first lithium composite oxide is insufficient.

[0093] In addition, when s1, which is the absolute value of the slope of the concentration gradient of cobalt in the first lithium composite oxide, is 2.0 or more, it means that the coating is biased toward the first lithium composite oxide and the coating of the second lithium composite oxide is insufficient. In this case, the effect of improving the stability of the initial particles existing in the surface portion of the second lithium composite oxide and the region relatively close to the center portion of the second lithium composite oxide is insufficient.

[0094] In one embodiment, s2, which is an absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the second lithium composite oxide, may satisfy the following formula 3.

[0095] Formula 3: 1.5<s2<3.0

[0096] When s2, which is the absolute value of the slope of the concentration gradient of cobalt in the second lithium composite oxide, is 1.5 or less, it means that the amount of cobalt in the second lithium composite oxide is insufficient. In this case, the effect of improving the stability of the initial particles existing in the surface portion of the second lithium composite oxide and the region relatively close to the center portion of the second lithium composite oxide is insufficient.

[0097] In addition, when s2, which is the absolute value of the slope of the concentration gradient of cobalt in the second lithium composite oxide, is 3.0 or more, it means that the coating is biased toward the second lithium composite oxide and the coating of the first lithium composite oxide is insufficient. In this case, the average particle size and grain boundary density are smaller than those of the second lithium composite oxide, which is advantageous for coating, but the absolute coating amount is insufficient, and thus, the effect of improving the stability of the first lithium composite oxide is insufficient.

[0098] Combining the above-mentioned Formulas 1 to 3, the cobalt in the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide has a concentration gradient decreasing from the surface portion to the center portion. Preferably, the absolute value of the slope of the above-mentioned cobalt concentration gradient decreasing from the surface portion to the center portion of the above-mentioned first lithium composite oxide should be controlled to be smaller than the absolute value of the slope of the above-mentioned cobalt concentration gradient decreasing from the surface portion to the center portion of the above-mentioned second lithium composite oxide.

[0099] Furthermore, when energy analysis-energy dispersive X-ray spectroscopy is performed on the surfaces of the first lithium composite oxide and the second lithium composite oxide, preferably, the second lithium composite oxide has a higher cobalt concentration than the first lithium composite oxide when measured at an accelerating voltage of 1.0 kV.

[0100] In this case, even if the absolute value of the slope of the cobalt concentration gradient decreasing from the surface toward the center of the second lithium composite oxide is greater than that of the first lithium composite oxide, the cobalt concentration in the center of the second lithium composite oxide can meet the prescribed standard.

[0101] Furthermore, for the same reasons as mentioned above, when energy analysis-energy dispersive X-ray spectroscopy is performed on the surfaces of the first lithium composite oxide and the second lithium composite oxide, preferably, the concentration of cobalt measured at an acceleration voltage of 30.0 kV is greater for the second lithium composite oxide than for the first lithium composite oxide.

[0102] In one embodiment, s1, which is the absolute value of the slope of the cobalt concentration gradient decreasing from the surface toward the center of the first lithium composite oxide, and s2, which is the absolute value of the slope of the cobalt concentration gradient decreasing from the surface toward the center of the second lithium composite oxide, may satisfy the following formula 4.

[0103] Formula 4: 1.0≤s2 / s1≤3.0

[0104] The fact that s2 / s1 calculated by the above formula 4 is greater than 3.0 means that the coating is excessively biased towards the second lithium composite oxide compared to the first lithium composite oxide, and the coating of the first lithium composite oxide is insufficient. In this case, the average particle size and grain boundary density are smaller than those of the second lithium composite oxide, which is conducive to coating. However, as the absolute coating amount is insufficient, the effect of improving the stability of the first lithium composite oxide is insufficient. In addition, due to the coating deviation of the first lithium composite oxide and the second lithium composite oxide, there is a concern that the performance degradation caused by the stability deviation of the first lithium composite oxide and the second lithium composite oxide in the bimodal positive electrode active material may be accelerated.

[0105] In addition, s2 / s1 calculated by the above formula 4 is less than 1.0, which means that the amount of cobalt in the above second lithium composite oxide is insufficient. In this case, the effect of improving the stability of the initial particles present in the surface portion of the above second lithium composite oxide and the region relatively close to the center portion of the above second lithium composite oxide is insufficient. In addition, s2 / s1 calculated by formula 4 is preferably greater than 1.5.

[0106] Furthermore, as described above, the first lithium composite oxide and the second lithium composite oxide may be composite particles including at least one primary particle capable of inserting and extracting lithium. In the case of a plurality of primary particles including the first lithium composite oxide and / or the second lithium composite oxide, the plurality of primary particles may exist as secondary particles of aggregates aggregated with each other.

[0107] The primary particle is a crystal grain (grain or crystallite), and the secondary particle is an aggregate formed by a plurality of primary particles. Pores and / or grain boundaries may exist between the primary particles constituting the secondary particles.

[0108] At this time, the first lithium composite oxide and the second lithium composite oxide in the bimodal positive electrode active material may have aggregation degrees of primary particles within different ranges.

[0109] The aggregation degree of the primary particles in the first lithium composite oxide and the second lithium composite oxide may be measured by the grain boundary density defined in the present application.

[0110] Specifically, the grain boundary density can be calculated by substituting the number of crystallites and the number of interfaces between the crystallites into the following formula 5, that is, after the first lithium composite oxide and the second lithium composite oxide are subjected to interface processing respectively, in the cross-sectional scanning electron microscope image obtained by photographing the cross-section of the first lithium composite oxide and the second lithium composite oxide using a scanning electron microscope (SEM), the crystallites located on a virtual straight line that crosses the center of the first lithium composite oxide and the second lithium composite oxide along the short axis direction.

[0111] Formula 5: Grain boundary density = (the number of interfaces between crystallites located on the above virtual straight line / the number of crystallites located on the above virtual straight line)

[0112] For example, in the case where the above-mentioned lithium composite oxide is a non-aggregated single particle composed of a single microcrystal, in the cross-sectional scanning electron microscope image of the above-mentioned lithium composite oxide, the number of microcrystals located on a virtual straight line crossing the center of the above-mentioned lithium composite oxide is 1, and thus, there is no interface between the microcrystals, and therefore, the grain boundary density calculated by the above-mentioned formula 1 is 0.

[0113] Furthermore, in the case where the above-mentioned lithium composite oxide is a particle formed by the aggregation of a small number of primary particles, in the cross-sectional scanning electron microscope image of the above-mentioned lithium composite oxide, the number of crystallites (primary particles) located on a virtual straight line crossing the center of the above-mentioned lithium composite oxide is 2, and thus there is an interface between the crystallites, so that the grain boundary density calculated by the above-mentioned formula 1 is 0.5.

[0114] Generally, the grain boundary density of the first lithium composite oxide as small particles is smaller than that of the second lithium composite oxide, and therefore, the coating of the grain boundary in the region near the center of the first lithium composite oxide is more favorable than that of the second lithium composite oxide. In this case, the surface and center of the first lithium composite oxide can be sufficiently coated with only a relatively small amount of coating raw material compared to the second lithium composite oxide.

[0115] However, for a bimodal positive electrode active material comprising the above-mentioned first lithium composite oxide as small particles and the above-mentioned second lithium composite oxide as large particles, the particle stability of the initial particles existing in the area relatively close to the center of the above-mentioned second lithium composite oxide can be improved while reducing the proportion of the coating biased on the first lithium composite oxide having a relatively small average particle size and grain boundary density.

[0116] Lithium secondary battery

[0117] According to another embodiment of the present invention, the present invention may provide a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. The positive electrode active material layer may include the positive electrode active material of various embodiments of the present invention. Therefore, the positive electrode active material is the same as that described previously, so for convenience, its specific description is omitted, and only the remaining structures not described above are described below.

[0118] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.

[0119] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.

[0120] In this case, the content of the positive electrode active material can be 80 weight percent to 99 weight percent, more specifically 85 weight percent to 98.5 weight percent, relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity characteristics can be shown, but it is not limited thereto.

[0121] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one or a mixture of two or more of them can be used. The above-mentioned conductive material may be included in an amount of 0.1 weight percent to 15 weight percent relative to the total weight of the positive electrode active material layer.

[0122] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated ethylene propylene diene monomer rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, the above-mentioned binder may be included in an amount of 0.1 weight percent to 15 weight percent.

[0123] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.

[0124] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when applied to prepare the positive electrode.

[0125] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.

[0126] Meanwhile, according to another embodiment of the present invention, an electrochemical device comprising the positive electrode may be provided. The electrochemical device may be a battery, a capacitor, etc., and more specifically a lithium secondary battery.

[0127] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not described above is described below.

[0128] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.

[0129] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0130] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.

[0131] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.

[0132] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; and SiO β(0<β<2), SnO2, vanadium oxide, lithium vanadium oxide, metal oxides capable of being doped and dedoped with lithium; or composites containing the above metal compounds and carbon materials such as Si-C composites or Sn-C composites, etc., and one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, and representative high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch-based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Mesophase pitches) and petroleum or coal tar pitch derived cokes (petroleum or coal tar pitch derived cokes) and other high-temperature sintered carbons.

[0133] Based on the total weight of the negative electrode active material layer, the negative electrode active material may be contained in an amount of 80 weight percent to 99 weight percent.

[0134] The binder is a component that helps to bind the conductive material, the active material and the current collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 to 10 weight percent of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.

[0135] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10 weight percent or less, preferably, 5 weight percent or less. There is no particular limitation on the conductive material as long as it does not induce chemical changes in the corresponding battery and has conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.

[0136] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.

[0137] Furthermore, in another embodiment, the negative electrode active material layer can also be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it. The negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent. Alternatively, the negative electrode slurry composition is poured on a separate support and then a thin film obtained by peeling off the support is laminated on the negative electrode collector.

[0138] In addition, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and has excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane coated with a ceramic component and a polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.

[0139] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.

[0140] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0141] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethylacetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methylethyl carbonate (MEC), ethylmethyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. carbonate, PC) and other carbonate solvents; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9 for use, excellent electrolyte performance can be shown.

[0142] The above-mentioned lithium salt can use compounds that can provide lithium ions used in lithium secondary batteries without limitation. Specifically, the above-mentioned lithium salt can use LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. Preferably, the concentration of the above-mentioned lithium salt needs to be used in the range of 0.1M to 2.0M. If the concentration of the lithium salt is included in the above range, the electrolyte has appropriate conductivity and viscosity, and therefore, excellent electrolyte performance can be shown, and lithium ions can be effectively moved.

[0143] In addition to the above electrolyte components, the electrolyte may also include one or more additives such as halogenated alkylene carbonate compounds such as bis(fluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1% by weight to 5% by weight relative to the total weight of the electrolyte.

[0144] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).

[0145] The shape of the lithium secondary battery of the present invention is not particularly limited, and may be cylindrical, prismatic, pouch, or coin-shaped using a can, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.

[0146] According to still another embodiment of the present invention, a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.

[0147] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.

[0148] Hereinafter, the present invention will be described in more detail by way of examples, but these examples are only for illustrating the present invention and should not be construed as limiting the scope of the present invention to these examples.

[0149] Preparation Example 1. Preparation of positive electrode active material

[0150] (1) Embodiment 1

[0151] (a) A NiCoAl(OH)2 hydroxide precursor (Ni:Co:Al=95:4:1 (at%)) as a first lithium composite oxide of small particles and a second lithium composite oxide of large particles were synthesized by a known co-precipitation method using nickel sulfate, cobalt sulfate and aluminum sulfate. The synthesized NiCoAl(OH)2 hydroxide precursor was heated to 400°C at a heating rate of 2°C per minute and then calcined at 400°C for 6 hours to be converted into an oxide precursor.

[0152] The average particle size (D50) of the oxide precursor of the first lithium composite oxide (first oxide precursor) was 4.0 μm, and the average particle size (D50) of the oxide precursor of the second lithium composite oxide (second oxide precursor) was 18.0 μm.

[0153] (b) The first oxide precursor and the second oxide precursor prepared in step (a) are weighed so that their weight ratio becomes 20:80, and then LiOH (Li / (Ni+Co+Al) molar ratio = 1.05) is added and mixed, and then the mixture is heated to 800°C at a heating rate of 2°C per minute in a sintering furnace while maintaining an O2 atmosphere, and then heat-treated for 12 hours to obtain an intermediate product.

[0154] (c) adding distilled water to the intermediate product and adding 7.0 weight percent of a cobalt sulfate aqueous solution so that the cobalt from the cobalt sulfate aqueous solution is 3.0 mole percent compared to the metal elements (Ni+Co+Al) other than lithium in the intermediate product, and stirring at 300 rpm for 1 hour, thereby coating the surfaces of the first oxide precursor and the second oxide precursor in the intermediate product with cobalt. After the reaction is completed, drying is performed at a temperature of 120° C. for 12 hours.

[0155] (d) For the above-mentioned intermediate product, an O2 atmosphere is maintained in a sintering furnace, and the temperature is increased to 700°C at a heating rate of 2°C per minute, and then heat-treated at 700°C for 12 hours to obtain a bimodal positive electrode active material in which a first lithium composite oxide as small particles and a second lithium composite oxide as large particles are mixed in a specified proportion.

[0156] (2) Embodiment 2

[0157] In step (c), a bimodal positive electrode active material was prepared in the same manner as in Example 1 except that stirring was performed at 400 rpm while adding the aqueous cobalt sulfate solution to react with the intermediate product.

[0158] (3) Embodiment 3

[0159] In step (c), a bimodal positive electrode active material was prepared in the same manner as in Example 1 except that 5.7 weight percent of a cobalt sulfate aqueous solution was used instead of 7.0 weight percent of cobalt sulfate.

[0160] (4) Embodiment 4

[0161] A bimodal positive electrode active material was prepared in the same manner as in Example 1 except that in step (c), the aqueous cobalt sulfate solution was added while stirring for 90 minutes instead of adding the aqueous cobalt sulfate solution while stirring for 1 hour.

[0162] (5) Embodiment 5

[0163] In step (b), the first oxide precursor, the second oxide precursor, LiOH (Li / (Ni+Co+Al) molar ratio = 1.05) and H3BO3 (B / (Ni+Co+Al) molar ratio = 0.015) are mixed and heat treated. In addition, a bimodal positive electrode active material is prepared in the same manner as in Example 1.

[0164] (6) Comparative Example 1

[0165] A bimodal positive electrode active material was prepared in the same manner as in Example 1 except that in step (c), the aqueous cobalt sulfate solution was added while stirring for 30 minutes instead of adding the aqueous cobalt sulfate solution while stirring for 1 hour.

[0166] (7) Comparative Example 2

[0167] In step (c), a bimodal positive electrode active material was prepared in the same manner as in Example 1, except that 9.6 weight percent of a cobalt sulfate aqueous solution was used instead of 7.0 weight percent of cobalt sulfate.

[0168] (8) Reference example

[0169] In step (b), the first oxide precursor, the second oxide precursor, LiOH (Li / (Ni+Co+Al) molar ratio = 1.05) and H3BO3 (B / (Ni+Co+Al) molar ratio = 0.015) are mixed and then heat treated. In step (c), a 9.6 weight percent cobalt sulfate aqueous solution is used instead of 7.0 weight percent of cobalt sulfate. Apart from this, a bimodal positive electrode active material is prepared in the same manner as in Example 1.

[0170] Preparation Example 2. Preparation of lithium secondary battery

[0171] A positive electrode slurry was prepared by dispersing 92 weight percent of each positive electrode active material prepared according to Preparation Example 1, 4 weight percent of artificial graphite, and 4 weight percent of polyvinylidene fluoride binder in 30 g of N-methylpyrrolidone. The positive electrode slurry was evenly coated on an aluminum film with a thickness of 15 μm and vacuum dried at a temperature of 135° C., thereby preparing a positive electrode for a lithium secondary battery.

[0172] Relative to the above-mentioned positive electrode, lithium foil was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separation membrane, and an electrolyte solution containing LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7 was used to prepare a button battery.

[0173] Experimental Example 1. Energy Analysis of Positive Electrode Active Material - Energy Dispersive X-ray Spectroscopy

[0174] Energy analysis-energy dispersive X-ray spectrometry was performed to measure the content of cobalt in the lithium composite oxide contained in the positive electrode active material prepared according to Preparation Example 1. When performing energy analysis-energy dispersive X-ray spectrometry, after the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) contained in the positive electrode active material prepared according to Preparation Example 1 were respectively screened, the acceleration voltage of the electron beam irradiated to the surface of the screened first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) was changed from 1 kV to 30 kV (1 kV, 3 kV, 5 kV, 7.5 kV, 10 kV, 12.5 kV, 15 kV, 20 kV, 30 kV), and the cumulative concentration (at%) of cobalt to a specific depth penetrated by the electron beam of each acceleration voltage was analyzed.

[0175] The absolute value of the slope of the cobalt concentration gradient measured in the region where the acceleration voltage of the electron beam irradiated onto the surface of the first lithium composite oxide (small particles) is from 1 kV to 30 kV is set to s1, and the absolute value of the slope of the cobalt concentration gradient measured in the region where the acceleration voltage of the electron beam irradiated onto the surface of the second lithium composite oxide (large particles) is from 1 kV to 30 kV is set to s2.

[0176] s1 and s2 showing the slope of the cobalt concentration gradient are calculated by setting the y-axis to the change in cobalt concentration (△at%) and the x-axis to the change in EDS acceleration voltage (△kV%), and are calculated by the average value obtained by summing the slopes of each measurement area.

[0177] The energy analysis-energy dispersive X-ray spectroscopy analysis results are shown in Tables 1 and 2. In Tables 1 and 2, s1 and s2 satisfy Formulas 1 to 3 defined in the present application, but examples that do not satisfy Formula 4 (1.0≤s2 / s1≤3.0) are recorded as reference examples.

[0178] Table 1

[0179]

[0180]

[0181] Table 2

[0182]

[0183] Referring to the results in Tables 1 and 2 above, in the first lithium composite oxide and the second lithium composite oxide contained in the bimodal positive electrode active material of Examples 1 to 5, cobalt forms a concentration gradient in which the concentration of cobalt decreases from the surface portion toward the center portion. At this time, it can be confirmed that the absolute value of the slope of the above-mentioned cobalt concentration gradient decreasing from the surface portion toward the center portion of the above-mentioned first lithium composite oxide is smaller than the absolute value of the slope of the above-mentioned cobalt concentration gradient decreasing from the surface portion toward the center portion of the above-mentioned second lithium composite oxide.

[0184] On the contrary, in the positive electrode active materials of Comparative Examples 1 and 2, it can be confirmed that although a concentration gradient is formed in which the concentration of cobalt decreases from the surface portion toward the center portion, the absolute value of the slope of the above-mentioned cobalt concentration gradient decreasing from the surface portion toward the center portion of the above-mentioned first lithium composite oxide is greater than the absolute value of the slope of the above-mentioned cobalt concentration gradient decreasing from the surface portion toward the center portion of the above-mentioned second lithium composite oxide.

[0185] (2) Cross-sectional scanning electron microscopy analysis of positive electrode active material

[0186] In order to measure the grain boundary density of the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) contained in the positive electrode active material prepared according to Preparation Example 1, the aggregation degree of primary particles in secondary particles confirmed from cross-sectional scanning electron microscope images was confirmed.

[0187] First, after screening the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) contained in the positive electrode active material prepared according to Preparation Example 1, cross-sectional scanning electron microscope images were taken using a FE-scanning electron microscope (Bruker) for the screened first lithium composite oxide (small particles) and the second lithium composite oxide (large particles).

[0188] Next, the number of crystallites and the number of interfaces between crystallites are substituted into the following formula 5 to calculate the grain boundary density, i.e., for multiple particles confirmed from the above cross-sectional scanning electron microscope image, the crystallites are respectively located on a virtual straight line passing through the center of the above particles along the short axis direction.

[0189] Formula 5: Grain boundary density = (the number of interfaces between primary particles located on the above virtual straight line / the number of primary particles located on the above virtual straight line)

[0190] Table 3 below shows the average value of the grain boundary density measured for a plurality of particles confirmed from the cross-sectional scanning electron microscope image.

[0191] Table 3

[0192]

[0193] Referring to the results in Table 3, it can be confirmed that the average value of the grain boundary density of the first lithium composite oxide (small particles) in the positive electrode active material prepared according to Preparation Example 1 is smaller than the average value of the grain boundary density of the second lithium composite oxide (large particles).

[0194] That is, relatively fewer primary particles exist inside the first lithium composite oxide having a smaller grain boundary density than the second lithium composite oxide, and therefore, fewer particles exist between the primary particles than in the second lithium composite oxide.

[0195] Furthermore, the average values ​​of the grain boundary density of the first lithium composite oxide and the second lithium composite oxide in the positive electrode active materials of Examples 1 to 5, Comparative Example 1, Comparative Example 2 and the reference example are almost similar. Therefore, it can be predicted that the difference in the cumulative concentration of cobalt at each acceleration voltage recorded in Tables 2 and 3 and the slope of the cobalt concentration gradient measured in the region where the acceleration voltage is from 1 kV to 30 kV are not caused by the difference in the grain boundary density recorded in Table 3.

[0196] Experimental Example 2. Evaluation of electrochemical characteristics of secondary batteries

[0197] For the lithium secondary battery (button battery) prepared in Preparation Example 2, a charge and discharge experiment was carried out using an electrochemical analyzer (Toyo, Toscat-3100) at a temperature of 25°C, a voltage range of 3.0V to 4.25V, and a discharge rate of 0.2 to measure the charge and discharge capacity.

[0198] Furthermore, for the same lithium secondary battery, after charging / discharging 50 times at 1C / 1C at a temperature of 25°C and a driving voltage range of 3.0V to 4.25V, the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention) was measured.

[0199] The above measurement results are shown in Table 4 below.

[0200] Table 4

[0201]

[0202] Referring to the results in Table 4, it can be confirmed that the charge and discharge efficiency and life efficiency of the lithium secondary battery using the positive electrode active material in which the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the second lithium composite oxide is greater than the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the first lithium composite oxide are improved.

[0203] In addition, in the case of the lithium secondary battery using the positive electrode active material of the reference example, the measured charge and discharge efficiency is almost similar to that of the lithium secondary battery using the positive electrode active material of Comparative Example 1 and Comparative Example 2, but it can be confirmed that the life efficiency is slightly improved. However, compared with the lithium secondary battery using the positive electrode active material of Examples 1 to 5, it can be confirmed that the life efficiency of the lithium secondary battery using the positive electrode active material of the above reference example is slightly lower.

[0204] Experimental Example 3. Stability Evaluation of Positive Electrode Active Material and Lithium Secondary Battery

[0205] (1) Evaluation of thermal stability of positive electrode active materials

[0206] In order to evaluate the thermal stability of the positive active material prepared according to Preparation Example 1, a thermogravimetric analyzer (TAInstruments, Q20) was used to measure the weight loss from 25°C to 350°C at a heating rate of 10°C / min under an Ar atmosphere at normal pressure. At this time, the onset temperature (on-set) of the weight loss (thermal decomposition) peak in each positive active material is shown in Table 5 below.

[0207] Table 5

[0208]

[0209] Referring to the results of Table 5 above, it is confirmed that the starting temperature of the weight loss (thermal decomposition) peak in the positive electrode active materials of Examples 1 to 5 is higher than that of the positive electrode active materials of Comparative Examples 1 to 3. That is, it can be seen that the thermal stability of the positive electrode active materials of Examples 1 to 5 is better than that of the positive electrode active materials of Comparative Examples 1 to 2.

[0210] (2) Measurement of gas generation from lithium secondary batteries

[0211] The lithium secondary battery prepared in Preparation Example 2 was charged to 4.25 V at a static current of 0.2 C and then stored at 60° C. for 14 days to measure the volume change of the lithium secondary battery caused by gas generation in the lithium secondary battery. The volume change measurement results are shown in Table 6 below.

[0212] Table 6

[0213]

[0214]

[0215] Referring to the results in Table 6, it can be confirmed that the volume change of the lithium secondary batteries using the positive electrode active materials of Examples 1 to 5 is smaller than the volume change of the lithium secondary batteries using the positive electrode active materials of Comparative Examples 1 to 3.

[0216] (3) Measure the DC-IR increase rate before and after the life of lithium secondary batteries

[0217] The DC-IR of the lithium secondary battery prepared according to Preparation Example 3 after one cycle at 1C (SOC 100) and after 50 charge and discharge cycles at 1C / 1C were measured, and the DC-IR increase is shown in Table 7 below.

[0218] Table 7

[0219] Classification DC-IR increase before / after life (Ω) Example 1 3.87 Example 2 2.92 Example 3 3.05 Example 4 3.35 Example 5 2.51 Comparative Example 1 7.91 Comparative Example 2 7.11 Reference example 7.05

[0220] Referring to the results in Table 7, it can be confirmed that the resistance increase after life of the lithium secondary batteries using the positive electrode active materials of Examples 1 to 5 is smaller than the resistance increase of the lithium secondary batteries using the positive electrode active materials of Comparative Examples 1 and 2.

Claims

1. A positive electrode active material, which is a bimodal positive electrode active material comprising a first lithium composite oxide as small particles and a second lithium composite oxide as large particles, characterized in that: The first lithium composite oxide has an average particle size of 7 μm or less, and the second lithium composite oxide has an average particle size of more than 7 μm and 30 μm or less. The weight ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is 5:95 to 50:

50. The first lithium composite oxide and the second lithium composite oxide contain at least nickel and cobalt, and the cobalt in the first lithium composite oxide and the second lithium composite oxide has a concentration gradient decreasing from a surface portion toward a center portion. When the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the first lithium composite oxide is set to s1 and the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center portion of the second lithium composite oxide is set to s2, s1 and s2 satisfy the following equations 1 to 4: Formula 1: s1<s2, Formula 2: 0.5<s1<2.0, Formula 3: 1.5<s2<3.0, Formula 4: 1.0<s2 / s1≤3.

0.

2. The positive electrode active material according to claim 1, characterized in that When energy analysis-energy dispersive X-ray spectroscopy is performed, the concentration of cobalt in the above-mentioned second lithium composite oxide measured at an acceleration voltage of 1.0 kV is greater than the concentration of cobalt in the above-mentioned first lithium composite oxide, and the above-mentioned concentration unit is at%. In the energy analysis-energy dispersive X-ray spectroscopy, for each surface of the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide, the cumulative concentration of cobalt from the surface of the first lithium composite oxide and the above-mentioned second lithium composite oxide to the depth penetrated by the above-mentioned electron beam is measured using an electron beam irradiated with an acceleration voltage increased from 1 kV to 30 kV.

3. The positive electrode active material according to claim 1, characterized in that When energy analysis-energy dispersive X-ray spectroscopy is performed, the concentration of cobalt in the above-mentioned second lithium composite oxide measured at an acceleration voltage of 30.0 kV is greater than the concentration of cobalt in the above-mentioned first lithium composite oxide, and the unit of the above-mentioned concentration is at%. In the energy analysis-energy dispersive X-ray spectroscopy, for each surface of the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide, the cumulative concentration of cobalt from the surface of the first lithium composite oxide and the above-mentioned second lithium composite oxide to the depth penetrated by the above-mentioned electron beam is measured using an electron beam irradiated with an acceleration voltage increased from 1 kV to 30 kV.

4. The positive electrode active material according to claim 1, characterized in that The first lithium composite oxide and the second lithium composite oxide are composite particles including at least one primary particle. The above-mentioned initial particles are represented by the following chemical formula 1: Chemical formula 1: Li w Ni 1-(x+y+z) Co x M1 y M2 z O2 in, M1 is at least one selected from Mn and Al, M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W and Cu, M1 and M2 are different from each other. 0.5≤w≤1.5,0 <x≤0.50,0≤y≤0.20,0≤z≤0.20。 5. The positive electrode active material according to claim 4, characterized in that At least one of the first lithium composite oxide and the second lithium composite oxide is a core-shell particle including a coating layer covering at least a portion of the surface of the primary particle and the composite particle, The coating layer comprises a metal oxide represented by the following chemical formula 2: Chemical formula 2: Li a M3 b O c in, M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Gd and Nd, 0≤a≤10, 0≤b≤8, 2≤c≤13, but the case where a and b are both 0 is excluded.

6. A positive electrode, characterized in that The positive electrode active material comprises the positive electrode active material according to any one of claims 1 to 5.

7. A lithium secondary battery, characterized in that: The positive electrode according to claim 6 is used.

Citation Information

Patent Citations

  • Cathode active material for secondary battery and secondary battery comprising same

    CN107251282A

  • Cathode active material for secondary battery, preparation method therefor, and secondary battery comprising same

    CN107534140A